1997
DOI: 10.1136/gut.40.2.253
|View full text |Cite
|
Sign up to set email alerts
|

In vitro influence of Phaseolus vulgaris, Griffonia simplicifolia, concanavalin A, wheat germ, and peanut agglutinins on HCT-15, LoVo, and SW837 human colorectal cancer cell growth.

Abstract: Background/Aims-Compared with nor-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…This effect was also found by Kiss et al 1997 with 3 different human colorectal cancer cell lines and by Lorea et al 1997 for PNA with melanoma cells. Camby et al 1997 found a weak stimulatory effect of PHA-L with astrocytic tumor cell lines during 48-96 hour incubations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This effect was also found by Kiss et al 1997 with 3 different human colorectal cancer cell lines and by Lorea et al 1997 for PNA with melanoma cells. Camby et al 1997 found a weak stimulatory effect of PHA-L with astrocytic tumor cell lines during 48-96 hour incubations.…”
Section: Discussionsupporting
confidence: 52%
“…Some of these lectins have demonstrated toxicity, to varying degrees, against some cancer cell lines in vitro, including: colon Kiss et al, 1997), breast (Valentiner et al, 2003), melanoma (Lorea et al, 1997;Litynska et al, 2001) and pancreatic cancers (Schwarz et al, 1999). These lectins have the potential to be used to target cancer cells for death.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also suggest that a wide range of concentrations of agents should be initially tested for their effects on cells. Sano et al (2000) found that migration of monocytes was best stimulated at 3μM galectin-3 while less stimulation occurred at 10μM or 0.01μM, while Kiss et al (1997) found lectin induced growth stimulation and lectin induced growth inhibition at different concentrations. They also found greater effects of a lectin on growth stimulation at low concentrations with no effect at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies with PNA indicate that this lectin acts in a cell type specific manner, often promoting proliferation and sometimes producing a toxic effect (Lee 1988;Caldero et al, 1989;McGarrity et al, 1991;Boland et al, 1992;Ryder et al, 1992;Chen et al, 1994;Kiss et al, 1997;Lorea et al, 1997;Jordinson et al, 1998;Yu et al, 2001;Singh et al, 2001;2006;Ohba et al, 2003;Cai et al, 2005). Valentiner et al (2003) in a model study showed that different lectins exerted different effects at specific concentrations on different breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation